Reading the wind: how middle managers assess the context for selling issues to top managers - DUTTON, JANE E.; ASHFORD, SUSAN J.; O’ NEILL, REGINA M.; HAYES, ERIKA; WIERBA, ELIZABETH E. (Strategic Management Journal, 1997)
Issue selling is an important mechanism for creating change initiatives in organizations. This paper presents two studies that examine what middle managers think about as they decide whether or not to sell strategic issues to top management. In Study 1 middle managers identify themes that indicate a favorable or unfavorable context for issue selling. Top management’s willingness to listen and a supportive culture were the most often named contributors to context favorability, while fear of negative consequences, downsizing conditions and uncertainty were thought to signal that a context was unfavorable for issue selling. Study 2 identifies factors that middle managers associate with image risk in the context of issue selling. Violating norms for issue selling, selling in a politically vulnerable way and having a distant relationship with top management were regarded as major contributors to a middle manager’s level of image risk. Both studies enrich our understanding of the social psychological mechanisms that undergird the strategic change process. © 1997 by John Wiley & Sons, Ltd.